The lady vanishes - White, Ethel Lina; Levy, Louis; White, Ethel Lina 1876-1944 (<<The>> Criterion Coll., 2007)
Travelers on a trans-European train are put up in a hotel for the night due to bad weather. Shortly after the journey begins in the morning, people begin to disappear. Bonus features include commentary; documentary; essays; and more.
Bildformat 1.33:1. - New, restored high-definition digital transfer
Orig.: Großbritannien 1938. - Sprache: Engl. - Enth. Bonusmaterial
Enth. audio commentary by film historian Bruce Eder ; "Crook's tour", a 1941 feature-length Charters and Caldicott adventure, available for the first time on home video, starring Basil Radford and Naunton Wayne reprising their beloved "The lady vanishes" roles ; excerpts from François Truffaut's legendary 1962 audio interview with Alfred Hitchcock ; "Mystery train", a new video essay about Hitchcock and "The lady vanishes" by Hitchcock scholar Leonard Leff ; stills gallery of behind-the-scenes photos and promotional art
Keywords: Railroad travel -- Europe -- Drama; Thrillers (Motion pictures); Europa; Film; Feature films; Fiction films; Foreign films; Spy films; Suspense films; Thriller - Feature